Anti-Amyloid-β Monoclonal Antibodies for Alzheimer’s Disease: Pitfalls and Promise - van Dyck, Christopher H. (Biol Psychiatry, 2017)
The majority of putative disease-modifying treatments in development for Alzheimer’s disease are directed against the amyloid-β (Aβ) peptide. Among the anti-Aβ therapeutic approaches, the most extensively developed is immunotherapy—specifically, passive immunization through administration of exogenous monoclonal antibodies (mAbs). Although testing of mAbs has been fraught with failure and confusing results, the experience gained from these trials has provided important clues for better treatments. This review summarizes the experience to date with anti-Aβ mAbs to enter clinical trials for Alzheimer’s disease and examines the evidence for clinical efficacy and the major problems with safety—i.e., amyloid-related imaging abnormalities. As mAbs differ considerably with regard to their epitopes and the conformations of Aβ that they recognize (monomers, oligomers, protofibrils, fibrils), the consequences of targeting different species are also considered. An often-cited explanation for the failure of anti-Aβ mAb trials is that they are set too late in the disease process. New trials are indeed evaluating treatments at prodromal and preclinical stages. We should expect to see additional studies of presymptomatic Alzheimer’s disease to join the ongoing prevention trials, for which mAbs continue to serve as the mainstay.